The influence of concentration of Nd-Fe-B powder in composite coating of optical fiber to the sensibility to external magnetic field - Radojević Vesna J.; Serbez T.; Aleksić R.; Nedeljković D.; Brajović Lj. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Multi-mode optical fiber with magnetic composite coating was investigated as an optical fiber sensor element (OFMSE) for magnetic field sensing The composite coating was formed with dispersions of permanent magnet powder of Nd-Fe-B in poly (ethylene-co-vinyl acetate)-EVA solutions in toluene. The influence of the applied external magnetic field on the change of intensity of the light signal propagate trough developed optical fibers sensor element was investigated. In this paper the influence of the content of magnetic powder in the composite coating on the optical propagation characteristics of optical fiber were particularly investigated.